Effects of different nano fillers on the physical and mechanical properties of medium density fiberboards (MDF) - Kızılkaya, Seyit Ali; Aydemir, Deniz Kırlı; Onat, Saadettin Murat; İstek, Abdullah; Onat, Saadettin Murat; İstek, Abdullah (My University, 2020)
In this study, the physical and mechanical properties of medium density fiber boards (MDF) produced with urea formaldehyde adhesive reinforced with nano-boron nitride (BN) and nano-titanium dioxide (TiO2) were investigated. 0.5% and 1.5% nano-filled urea formaldehyde adhesives were used in the production of test samples. The density, thickness swelling, water uptake, internal bond strength, bending strength, modulus of elasticity in bending and SEM analysis of the boards prepered were determined. According to the laboratory tests conducted, there was no significant change in the density of the boards after nano filling. Physical properties such as water intake and thickness swelling were determined to decrease with the addition of nano particles. The mechanical properties of the boards increased with the addition of both nano-BN and TiO2. According to the a results of thermogravimetric analysis, it has been determined that the thermal stability of urea formaldehyde adhesive with TiO2 is increased and maximum mass loss temperatures are higher than the addition of nano-BN. The morphological structure of the urea formaldehyde adhesive was visualized with an electron microscope, and the nanoparticle dispersions were displayed and the particles were also analyzed by EDAX analysis. As a result, it has been determined that MDFs prepared with nanoparticle adhesives have improved physical, mechanical and thermal properties. Particularly, all samples with nano particles have been achieved the standards required in their mechanical properties. As a result, it can be sad that the adding nano-particles have positive effect on the physical and mechanical properties of the panels.
Keywords: Nanobilim ve Nanoteknoloji; Malzeme Bilimleri; Özellik ve Test; İmalat Mühendisliği; Malzeme Bilimleri; Biyomalzemeler